Superior Sagittal Sinus Invasion by Malignant Glioma: Case Report and Literature Review - Figueiredo, Gonçalo Cerdeira; Moreira, Sérgio; Pinheiro, Célia; Calheiros, Alfredo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Anaplastic oligodendrogliomas (AOs) correspond to ∼ 23% of all oligodendrogliomas. They correspond to a tumor with malignant histological characteristics, focal or diffuse, associated with a worse prognosis. In the present case report, we describe the case of a 30-year-old female submitted to resection of a right parietal lesion whose histology showed to be an AO. She underwent complementary treatment with chemotherapy and radiotherapy according to the Roger Stupp protocol. Four years after the initial diagnosis, there was tumor recurrence within the superior sagittal sinus, with no evidence of recurrence elsewhere. In the literature, we have found no similar published case reinforcing the rarity of this condition
Keywords: anaplastic oligodendroglioma; superior sagittal sinus